Prognostic Value of Rapid Test for Diagnosis of Dengue in Nepalese Patients during 2010 Epidemic - Pun, R; Shah, Y; Gupta, GP; Sherchand, SP; Pandey, BD (Kathmandu University Medical Journal, 2012)
Background Dengue is an emerging vector borne disease in Nepal and rapid diagnostic test is important for early diagnosis of the disease. Objectives The aim of the study was to evaluate the diagnostic accuracy of commonly used rapid immunochromatographic test kit in Nepal during 2010 dengue epidemic and to assess disease burden of dengue. Methods A total of 131 acute and nonacute serum samples were collected during recent epidemic of dengue in 2010 from clinically suspected Nepalese patients of different hospitals. Rapid immunochromatographic test kit was used for early diagnosis and enzyme immunosorbent was chosen as a reference assay. Results The sensitivity and specificity of rapid test was 70% and 76.54% respectively whereas the prevalence of the disease was 38.17%. The odds ratio for males was 1.8 however; the association with the disease was statistically not significant. Conclusion The diagnostic accuracy of rapid immunochromatographic test for dengue diagnosis was low (k=0.46). So, it should be substituted by highly sensitive test device for prompt diagnosis and health personnel should consider appropriate timing of sample collection for better performance of rapid test. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 7-10 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6905